Economic potential of biotechnologies: Challenges and windows of opportunity - Chazhaev Muslim (BIO Web of Conferences, 2023)
Biotechnology is emerging as a transformative force with the potential to reshape industries and economies. This article delves into the economic potential of biotechnologies and explores the challenges and opportunities they present. The analysis is rooted in current global trends, innovations, and advancements in biotechnological research and applications. It also addresses the economic impact of biotechnology in various sectors, including healthcare, agriculture, energy, and the environment. The study highlights key challenges faced by biotech industries, such as regulatory hurdles, ethical concerns, and intellectual property issues, and proposes strategies to overcome these obstacles. Moreover, it identifies windows of opportunity for economic growth and sustainability through biotechnological innovations. The article concludes by emphasizing the need for strategic investment, interdisciplinary collaboration, and forward-thinking policies to unlock the full economic potential of biotechnologies and promote global prosperity.